IMPLEMENTASI SERVER VoIP (Voice Over Internet Protocol ) PADA KANTOR KECAMATAN SALING KABUPATEN EMPAT LAWANG - Armanto, Armanto armanto (LPPM UNIVERSITAS BINA INSAN, 2018)
Implementation of VoIP Server At Sub-District Office of Saling Regency Empat Lawang has building structure which has many room. In case communicate sometimes takes a fast time. Like a meeting to be made at that moment. For that to be helpful in time and efficient then it can be applied Conference Call at Saling sub-district office. In this study the network used is Local Area Network (LAN), Using server3CX Phone System, while in developing the system used NDLC (Network Development Life Cycle) method. With VoIP Server Implementation In Sub-District Office of Saling Regency Empat Lawang can make inter-space communication to be efficient and reduce the cost of usage of mobile phone pulse which is too high. Keywords: VoIP server, 3CX Phone System, Conference